(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article is shown features of political protest in modern society, reasons and factors, depending on changes of forms of political protest. Also in article author explores the character of traditional and modern forms of political protest in society, role of Internet and social networks and its influence on dynamics of political protest. Keywords: politics, social protest, political system, political stability, political regime, deprivation, civil society.